Transnational security - Maras, Marie-Helen, 1979- (Boca Raton : CRC Press/Taylor & Francis Group, 2015)
Globalization and the easy movement of people, weapons, and toxins across borders has transformed security into a transnational phenomenon. Preventing transnational security threats has proven to be a very difficult challenge for governments and institutions around the world. Transnational Security addresses these issues, which are at the forefront of every global security professional's agenda. This book analyzes the most pressing current transnational security threats, including weapons of mass destruction, terrorism, organized crime, cybercrime, natural disasters, human-made disasters, infectious diseases, food insecurity, water insecurity, and energy insecurity. It considers the applicable international laws and examines how key international organizations are dealing with these issues. The author uses a combination of theory and real-world examples to illustrate the transnational nature of security risks. By providing a detailed account of the different threats, countermeasures, and their implications for a number of different fields--law, public policy and administration, security, and criminology--this book will be an extremely useful resource for academicians, practitioners, and graduate and upper-level undergraduate students in these areas. Transnational Security provides a comprehensive text for graduate and advanced undergraduate courses on transnational security (global security, human security, or security studies). It can also be used for crisis management and disaster preparedness courses, as well as global governance courses and courses that focus on specific transnational security threats. Since it covers global transnational security practices, this book should also be of interest to security officials, UN employees, nongovernmental organizations (NGOs), and researchers in the field.
1. Transnational security: an introduction -- 2. Decisions under uncertainty: theories and practice in security studies -- 3. Weapons of mass destruction and nonproliferation -- 4. Transnational terrorism -- 5. Transnational organized crime -- 6. Cybersecurity -- 7. Natural disasters: a forgotten security risk? -- 8. Human-made disasters -- 9. Infectious diseases -- 10. Security issues in conflict and post-conflict societies -- 11. The fight for natural resources: seeking food and water security -- 12. Energy security: current issues -- 13. The future of transnational security: concluding remarks.
Includes bibliographical references and index.
Keywords: National security; Security, International; Terrorism -- Prevention